2022
DOI: 10.1126/sciadv.abm9844
|View full text |Cite
|
Sign up to set email alerts
|

Developmental dynamics of the neural crest–mesenchymal axis in creating the thymic microenvironment

Abstract: The thymic stroma is composed of epithelial and nonepithelial cells providing separate microenvironments controlling homing, differentiation, and selection of hematopoietic precursor cells to functional T cells. Here, we explore at single-cell resolution the complex composition and dynamic changes of the nonepithelial stromal compartment across different developmental stages in the human and mouse thymus, and in an experimental model of the DiGeorge syndrome, the most common form of human thymic hypoplasia. Th… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
16
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(17 citation statements)
references
References 88 publications
1
16
0
Order By: Relevance
“…3f, Fig. S5m,n; Table S7 ): Gain of CNVs led to a loss of genes involved in trunk NC differentiation and cell death (e.g., chromaffin cell-associated gene PEG3 and WNT-antagonist SFRP1 58 ) and induction of NB-associated transcripts such as MSX2 and CNTNAP2 59 ( Fig. 3f ).…”
Section: Resultsmentioning
confidence: 99%
“…3f, Fig. S5m,n; Table S7 ): Gain of CNVs led to a loss of genes involved in trunk NC differentiation and cell death (e.g., chromaffin cell-associated gene PEG3 and WNT-antagonist SFRP1 58 ) and induction of NB-associated transcripts such as MSX2 and CNTNAP2 59 ( Fig. 3f ).…”
Section: Resultsmentioning
confidence: 99%
“…Critical receptor ligand interactions between the thymic epithelial and lymphoid compartment are well described 4,87 . In addition, a recent report highlighted the contribution of the non-epithelial non-lymphoid compartment to thymic development in murine models of health and disease 33 . To investigate the unique role the microenvironment plays in human thymic development, we used Cellphone DB v2.0.…”
Section: Resultsmentioning
confidence: 99%
“…Our studies build upon recent advances defining mouse and human thymic microenvironment and architecture using single cell transcriptomics 16,33 . These studies demonstrated an abundance of novel and unique thymic cell subpopulations which had evaded discrimination by conventional analytic metrics.…”
Section: Introductionmentioning
confidence: 99%
“…Single cell transcriptomic analyses have uncovered an unexpected heterogeneity within many cell populations of a seemingly identical phenotype. Cells of the thymic stromal compartment constitute no exception to this observation ((Baran-Gale et al, 2020;Bornstein et al, 2018;Dhalla et al, 2020;Handel et al, 2022;Miller et al, 2018). The apparent lack of suitable cell surface markers identifying unequivocally TEC subpopulations identical to individual TEC subtypes precludes the isolation of live TEC and their ex vivo functional analysis.…”
Section: Discussionmentioning
confidence: 99%
“…Thymic epithelial cells (TEC) constitute the major cellular element of the stromal scaffold (Anderson et al, 1993; Anderson and Takahama, 2012; James et al, 2021). Other cellular components of the stroma are different mesenchymal cell types and endothelial cells (Handel et al, 2022; James et al, 2021). TEC attract blood-borne lymphoid progenitors, commit them to a T cell fate, provide the molecular cues essential for expansion and differentiation, and shape the T cell antigen receptor (TCR) repertoire via stringent processes of positive and negative selection based on the cells’ antigen specificity (Kadouri et al, 2020; Klein et al, 2014; Zlotoff and Bhandoola, 2011).…”
Section: Introductionmentioning
confidence: 99%